Dressed for Freedom : The Fashionable Politics of American Feminism - Rabinovitch-Fox, Einav, 1981- (Book collections on Project MUSE., 2021)
"Often condemned as a form of oppression, fashion could and did allow women to express modern gender identities and promote feminist ideas. Einav Rabinovitch-Fox examines how clothes empowered women, and particularly women barred from positions of influence due to race or class. Moving from 1890s shirtwaists through the miniskirts and unisex styles of the 1970s, Rabinovitch-Fox shows how the rise of mass media culture made fashion a vehicle for women to assert claims over their bodies, femininity, and social roles. She also highlights how trends in women's sartorial practices expressed ideas of independence and equality. As women employed new clothing styles, they expanded feminist activism beyond formal organizations and movements and reclaimed fashion as a realm of pleasure, power, and feminist consciousness. A fascinating account of clothing as an everyday feminist practice, Dressed for Freedom brings fashion into discussions of American feminism during the long twentieth century"--